Kelayakan dan Strategi Pengembangan Usaha Pembenihan Ikan Patin di CV Mika Distrindo - Pindo Witoko; Rizal Syarief; Sapta Raharja (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
The development of larva production of Patin catfish has great potential to meet market demand. CV Mika Distrindo is the one of company that need a development strategy to increase production to meet demand of Patin catfish larva. The aims of this study were: (1) to obtain information on the production process of breeding; (2) to know the feasibility of breeding; and (3) to carry out the strategy of seeding to obtain maximum profit. Method of analysis was done with (1) a descriptive analysis of the production process for a portrait Patin catfish hatchery; (2) Analysis of the feasibility using NPV, IRR, Net B/C Ratio, Gross B/C Ratio, PBP, and BEP; (3) Analysis of internal and external matrix are using IFE and EFE matrix, and in combination in a matrix of IE; 4) SWOT matrix analysis to formulate strategic alternatives; and 5) Analysis QSPM for alternative decision priorities. The study results shows that CV Mika Distrindo is feasible because the business get the financial benefit. Indications in terms of financial feasibility are known from Rp516.660.510 of NPV; 21.42% of IRR; 5.57 of Gross B/C Ratio; 4.05 of Nett B/C Ratio; 10 months and 5 days of PBP and 2.698.006 of larva production or Rp539.601.139,60 of the value of sales. IFE score is 2.511 and EFE score is 2.565 (medium position). The Company core strategy is Growth/Stability Strategy. The SWOT analysis obtains formulation of strategies including the use of advances in technology, expansion of marketing network, strengthening capital, increasing sales volume, doing partnerships, taking advantage of investors, increase customer loyalty, maintain larva quality, improved system management and collaboration with stakeholders.Key words: Patin catfish hatchery, feasibility analysis and business development strategy